Validation of Malay Caregiver Strain Index - Othman, Zahiruddin; Wong, Siong Teck (Yuzuncu Yil University, 2014)
This study aimed to validate the Caregiver Strain Index (CSI), a self-administered questionnaire for rating burden and strain related to care provision, for use in local clinical practice. The CSI was translated into Malay language using forward and back translation method. The final Malay version was administered to 50 caregivers of post-stroke patients attending the medical clinic, Hospital Umum Sarawak in December 2011. The Malay Caregiver Strain Index (CSI-M) has a good face and content validity as well as internal consistency (Cronbach’s alpha 0.79). In conclusion, the CSI-M is a reliable tool for assessment of burden experienced by caregivers in Malaysia.